(untitled) (Bulletin KNOB, 2004)
In this article the financing of the building process of castle De Haar in the period between 1891 and 1897 is sketched. This period was important because from the various documents it appears that the plans for the restoration became final in those years. From 1895 the object of the work was to enable the baron and baroness to invite their first guests at their new country estate by the summer of 1897. This period was also important because the baron was engaged in a ’war on two fronts’. Not only did he wish to restore his ancestral domain, but also the ruins of castle De Haar. For this purpose the baron had an ample, but not unlimited budget at his disposal. Soon the extent of the work had become so large that the baron fell into an arrears of payment. This increased so much that he was forced to give his newly acquired real estate in pledge as security for various loans so as to be able to pay the day-to-day costs. A closer examination of the records suggests that on the one hand the costs were much higher than estimated due to the method used, which was quite normal in the case of complicated buildings, and on the other hand that the baron could not write out cheques unlimitedly.